Prediction and Risk Group of Coronavirus Disease 2019 Protection Behaviors in the Community among Juveniles in Northern Region of Thailand - Yaemyuean, Anan; Nonthachot, Perawat; Ekphachaisawat, Teerapatra (Community and Social Development Journal, 2023)
The coronavirus disease 2019 protection behavior in the community of juveniles in the northern region can have an impact on the lifestyles of people in the community if the juveniles ignore or do not follow protective measures against coronavirus disease 2019. The research aims to 1) identify significant predictors and prediction of psychological traits and situations involving the coronavirus disease 2019 protection behavior in the community and 2) investigate risk groups and protective factors. The sample consists of 600 juveniles obtained from the multi-stage quota random sampling. The analytic statistics used to test the hypotheses were the enter and stepwise methods of multiple regression analysis and the three - way analysis of variance. The findings revealed that psychological traits, situations, and psychological states can predict 56.80% of the coronavirus disease 2019 protection behavior in the community. The most significant predictor is a positive attitude towards the coronavirus disease 2019 protection behavior (β=.29), followed by future orientation and self-control regarding the coronavirus disease 2019 protection (β=.27), love-reasoned child rearing practice (β=.22), observance of media on the coronavirus disease 2019 protection behaviors (β=.18), observance of their parents’ coronavirus disease 2019 protection behaviors (β=.13), moral disengagement concerning Covid-19 prevention (β=.10), and emotional quotient (β=.08), respectively. Additionally, it was found that male juveniles and juveniles who lack protective equipment are at high risk and require urgent care. The research recommended protective development guideline to raise awareness of juveniles about the coronavirus disease 2019 protection behavior in the community with the coordination of public and civic sectors in the community.